Knowledge and Adoption of Marigold Cultivation Practices of Women Farmers in Gurugram District of Haryana - Yadav, Pankaj; Dahiya, D. S. (Indian Journal of Extension Education, 2020)
The study was conducted in Gurugram district of Haryana state. Two blocks Farrukh Nagar and Gurugram were selected randomly and from each selected block, fifty women farmers who were involved in marigold cultivation selected randomly, thus making a total of 100 respondents. The study revealed that, majority of the respondents were middle aged, having small family size, living as joint families, and having small landholding size. Majority of the respondents were found listening to radio krishi programmes as their mass media exposure. In case extension contacts majority of the respondents were found in contact with the ADO/VEW whereas risk orientation of majority of the respondents was at low level. Regarding concept, importance, harvesting, packing and marketing of marigold majority of the respondents had medium level of knowledge and adoption.